Essential Approach of Maintenance Management System of Office Building - Othman, Masyatul Husna; Othuman Mydin, Md Azree (Eftimie Murgu University of Resita, 2013)
Buildings will be worn-out, dilapidated and dirty as time goes by; but with good maintenance management we can at least prolong the lifespan of building longer as well as provide the building services and keep the building performance at it ultimate level. The importance of carrying out a systematic and routine maintenance works as part of works to conserve building performance is often neglected due to various factors including due to misunderstanding on the needs of the maintenance works itself and budget allocated. Thus, the purpose of the present study was to evaluating the level of maintenance management and quality of services in office buildings. This study also sought to answer the following question to determine the basic approach of maintenance management system used for office buildings..